2002
DOI: 10.1002/app.11366
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase polymerization of butadiene. Data acquisition using minireactor technology and particle modeling

Abstract: Minireactor technology has been used for kinetic studies on polymerization kinetics, phase equilibrium, and mass transfer on a very small scale. There is a nonlinear influence of temperature and pressure on the polymerization rate. The phase equilibrium can be described by a Flory-Huggins approach, with a temperature-dependent interaction parameter. The diffusion coefficient seems to be slightly pressure dependent, and the temperature dependence can be described with an Arrhenius equation. A simple formal kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…A simple chemical model was applied without considering physical processes, even though it was shown that catalyst activation was mainly a result of support fragmentation. The model presented is based on that of Bartke 33 and is valid for gas-phase polymerization of propylene with the nonsupported and silica-supported Ziegler-Natta catalysts (Cat E and Cat B). Average particle activity determined using video microscopy at 45°C and 5 bar in the absence of hydrogen or comonomer was simu- Figure 14 shows the activity, measured by video microscopy, along with the simulated activities of Cat E and Cat B versus reaction time.…”
Section: Modeling Of Average Particle Activity Of Polymerizationmentioning
confidence: 99%
“…A simple chemical model was applied without considering physical processes, even though it was shown that catalyst activation was mainly a result of support fragmentation. The model presented is based on that of Bartke 33 and is valid for gas-phase polymerization of propylene with the nonsupported and silica-supported Ziegler-Natta catalysts (Cat E and Cat B). Average particle activity determined using video microscopy at 45°C and 5 bar in the absence of hydrogen or comonomer was simu- Figure 14 shows the activity, measured by video microscopy, along with the simulated activities of Cat E and Cat B versus reaction time.…”
Section: Modeling Of Average Particle Activity Of Polymerizationmentioning
confidence: 99%
“…The optical part of the video microscope system consists of a video camera (Pieper, resolution 720 6 576 pixel), a halogen lamp from Schölly Fiber Optics GmbH, light cables, and a light microscope (Carl Zeiss) with three magnifications (4,8,16). …”
Section: Video Microscopy Systemmentioning
confidence: 99%
“…The minireactor is equipped with a view port on its top that enables the direct observation of the growing particles. Details of the minireactor for video microscopic studies and photo analysis technique is shown by Zöllner [2,3] and Bartke [4].…”
Section: Video Microscopy Systemmentioning
confidence: 99%
See 2 more Smart Citations